Child Participation in Family-School Cooperation - Maleš, Dubravka (2010)
The paper discusses the cooperation between family and school from the perspective of the UN Convention on the Rights of the Child (1989). Article 12 of the Convention distinctly emphasizes the right of the child to express his or her own views freely in all matters affecting him or her, as well as the right that the views be given due weight in accordance with the child’s age and maturity, thus ensuring the child’s active participation in his or her environment. Given that the principal purpose of the cooperation between family and school is the child’s well-being, it is reasonable to expect the child’s participation in the situations of direct parent-teacher cooperation. The paper seeks to give answers whether the requirement for child participation is being fulfilled in schools in the Republic of Croatia. The theoretical part of the paper is grounded on the contemporary scientific findings in family-school cooperation and the role of the child in the process, while the empirical part presents the research results of the existing practices of child participation in family-school cooperation in several primary and secondary schools in Croatia. As a theoretical basis for the research, Hart’s (1995) ‘Ladder of Participation’ model has been used, whereas the results can serve as guidelines for improving the existing school practices and introducing changes in school legislation relating to the cooperation with parents.